Community Attitudes and Decisions in Choosing a Health Center as a Health Service Facility in Lembang Laang Tanduk, Tampak Selatan, Rantepao District - Sri Angriani; Baharuddin Baharuddin (Humanistic Network for Science and Technology (HNST), 2021)
The existence of a community health center as the spearhead of health services in Indonesia is faced with various problems such as a decrease in budget allocations and a lack of health personnel. This study aims to analyze the relationship between attitudes and decisions about choosing a community health center as a health service facility, especially at the Laang Tanduk. The study design was cross-sectional with respondents from the health center customers who were selected by purposive sampling technique. Data were collected through filling out a questionnaire and tested the hypothesis using the Chi-square test. The results showed that the p-value was less than 0.05, so it was concluded that attitudes were related to the community's decision to choose a health center as a health service facility. Keywords: public health center, decision to choose, attitude, community